Medical Sterilization and Modern Technologies: A Comprehensive Review of Current Methods and Emerging Innovations (The Review of Diabetic Studies, 2024)
Sterilization of medical instruments is a critical component of infection control in healthcare settings. This comprehensive review examines traditional and modern sterilization methods, evaluating their effectiveness, safety, and practical applications. The paper explores steam sterilization, low-temperature gas plasma technologies, ultraviolet-C disinfection, and emerging innovations in medical device sterilization. With the increasing complexity of medical devices and growing concerns about environmental safety, healthcare facilities are transitioning toward more advanced sterilization modalities. This review synthesizes current evidence on sterilization efficacy, material compatibility, and operational considerations to guide healthcare professionals in selecting appropriate sterilization methods. The findings indicate that while steam sterilization remains the gold standard for heat-stable instruments, vaporized hydrogen peroxide and UV-C technologies offer promising alternatives for heat-sensitive devices, with implications for improving patient safety and reducing healthcare-associated infections.